Transformasi Sosial Keagamaan Masyarakat Muslim Lamongan Tahun 1990-2017: Religious Social Transformation of Lamongan Muslim Community in 1990-2017 - Irsyadah, Naylatul (Nur Science Institute, 2022)
Socio-religious transformation is a change that occurs in Javaneve society, especially in religious field. Changes in Javanese society that are getting greener show the occurrences of islamization which encourage the deepening and improvement of Islamic religiosity. This change is marked by the transformation of society towards Islamic orthodoxy (obedience to Islamic law). The benefit of this research is to provide knowledge about the history of clothing or the history of lifestyle in Indonesia, especially in Java. This study uses historical research methods. This research discuss about weddings and the bride's fashion. The stages in the historical research method are: (1) Heuristics or data collection, (2) Verification or resource criticism, (3) Interpretation or analysis of historical facts, and (4) Historiography or historical writing. The findings of this study are that the traditions surrounding the wedding and the bride's attire do not happen all at once but gradually. The transformation of tradition around marriage occurs in the form of: (a) The term of people who do bridal makeup from dukun manten to pemaes manten then changes to MUA; (b) Hajatan and entertainment of wedding celebration; (c) Bride's make-up. Meanwhile, the change in bridal attire took place through five phases, the changes are: a) the phase of traditional Javanese bridal attire, b) the blending phase of Javanese and European attire, c) the first phase of the presence of Muslim bridal attire, d) the massive phase of Muslim bridal attire, e) the domination phase of Muslim bridal attire. The shift in tradition around weddings and wedding attire itself is not only due to the influence of Islamization, but also due to Modernization.